Methodological Approaches to Assessing the Efficiency of Personnel Management in Companies - LEBEDEV, Kostyantyn Anatol'evich; REZNIKOVA, Olga Sergeevna; DIMITRIEVA, Snezhana Dmitrievna; AMETOVA, Elmaz Ismetovna (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).20, 2018)
This paper looks into the development of methodological approaches to assessing the efficiency of personnel management in an enterprise. The authors establish that appraising personnel is a crucial component of the system of personnel management in an enterprise. It acts as a powerful tool for motivating work. The authors suggest determining the content of the company’s major types of work activity and its major end results through the use of a structural-diagnostic model for assessing the efficiency of personnel management that characterizes the mechanism underlying the interaction between the 3 major operands involved in the production of services: people, factors, and organization. The model lets you assess the content and efficiency of personnel management based on the findings of analyses of positions of employment, the staff recruitment system, the staff training system, compliance with work discipline, labor productivity, career planning, and pay. The authors prove that as primary assessment criteria of the efficiency of HR policy such indicators as labor efficiency, compliance with legislation, satisfaction with work, no-shows at work, employee turnover, the number of conflicts and complaints, and the accident frequency rate could be used.